ANALISIS GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 SAMPAI DENGAN TAHUN 2018 - Ryan Muhammad Muttawaqil Billah; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to determine and analyze that managerial ownership, institutional ownership, and company size have an impact on financial performance in financial companies listed on the Indonesia Stock Exchange from 2014 to 2018. The results of the classical assumption test show that the normality test of research is normally distributed. the result of the Asymp value. Sig (2-tailed) of 0.200 so that the value is above the significant level of 0.05. Multicolonearity test there is no multicolonearity between the independent variables in the regression model, the results of the tolerance calculation for the independent variables are more than 0.10 and the results of the valance inflation factor (VIF) have a VIF value below 10. Heteroscedasticity test: there is no heteroscedasticity. Autocorrelation test: the DW value is 2.018, where the value of du in the Durbin-Watson table with n showing a sample of 16, and k which shows the number of independent variables of 3 is 0.857 for dL and 1.728 for dU. So that the DW value obtained from the test belongs to the distance dU <d <4-dU, with a dU table value of 1.728 <2.018 <2.272 indicating that the model used is free from autocorrelation. The R2 value of this study is 0.517, this value means that the total variance of related party transactions around an average of 51.7% can be explained by the relationship between managerial ownership, institutional ownership, and company size together. While the remaining 48.3% is influenced by other unexplained factors.